Análisis del impacto de la deuda externa sobre el crecimiento económico en el Ecuador - Hidalgo Flor, Luís Eduardo (2009)
This paper develops a study,which examinies the relationship between external debt, private invesment and growth in Ecuador in the period 1970 to 2007, to quantify the effects on the economy of an external debt overhang.